The Effect of Influencer Marketing on Buying Interest, Satisfaction, and Loyalty Among Gen Z Consumers of MSME Culinary Products in Indonesia - Muammar Khaddapi; Burhanuddin Harahap; Elva Amrin; Indrawan (Fundamental and Applied Management Journal, 2026)
This study examines the effect of influencer marketing on buying interest, consumer satisfaction, and loyalty among Gen Z consumers of MSME culinary products in Indonesia. The background of this study is the growing use of influencers as a digital marketing communication strategy. Still, their effectiveness in shaping Gen Z consumers' long-term behavior remains inconsistent. The SEM-PLS method is used in this quantitative investigation. A structured survey via Google Forms was used to collect data from 218 respondents. Customers who have purchased food items endorsed by influencers comprise the target sample. The findings demonstrate that influencer marketing significantly influences buying interest and customer satisfaction, supporting H1 and H2. Specifically, influencer credibility, attractiveness, and product congruence effectively stimulate consumers' initial interest in culinary products promoted through social media. However, influencer marketing was found to have no significant direct effect on customer loyalty, and the sequential mediation of buying interest and satisfaction was also not supported, leading to the rejection of H3 and H3a. Product and service quality is the primary factor that determines favorable repurchases and referrals, as satisfaction has been demonstrated to have a strong, beneficial influence on loyalty. Furthermore, the direct effect of influencer marketing on loyalty was negative, and the mediating path through buying interest and satisfaction was also negative. According to research, influencer marketing effectively increases buy intent, but sustained, fulfilling consumption is the only way to foster loyalty.